2018
DOI: 10.1155/2018/4083439
|View full text |Cite
|
Sign up to set email alerts
|

A Coupled One-Dimensional Numerical Simulation of the Land Subsidence Process in a Multilayer Aquifer System due to Hydraulic Head Variation in the Pumped Layer

Abstract: After exploitation of groundwater had been reduced and the groundwater level of the confined aquifer had risen, land subsidence was observed to continue rather than cease for several years according to the layer-wise mark monitoring data in Xi'an. To analyze the phenomena, a numerical model of a coupled one-dimensional multilayer aquifer system is developed to represent land subsidence due to hydraulic head variation in the pumped layer. The numerical simulation results show that the pressure head in other lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…where δ t is the Dirac delta function and t is the time. It is obvious that the substitution of equation 7into equation (6) gives the constitutive relationship of the linear elastic model if α = 0, while it produces that of the standard Merchant model if α = 1. That is, both the linear elastic model and standard Merchant model are two special cases of the fractional-derivative Merchant model.…”
Section: Mathematical Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…where δ t is the Dirac delta function and t is the time. It is obvious that the substitution of equation 7into equation (6) gives the constitutive relationship of the linear elastic model if α = 0, while it produces that of the standard Merchant model if α = 1. That is, both the linear elastic model and standard Merchant model are two special cases of the fractional-derivative Merchant model.…”
Section: Mathematical Modelmentioning
confidence: 99%
“…In general, the bottom boundary of the aquitard connected to the nearly rigid sandy stratum yields zero deformation [29]; thus, the settlement of the aquitard can be obtained by integrating equation (6) along the vertical direction. The result is…”
Section: Geofluidsmentioning
confidence: 99%
See 2 more Smart Citations
“…Note a growing consensus has suggested that ground subsidence occurs lagging behind the pumping activity (Kearns et al, 2015), and the duration of land subsidence induced by deep pumping is longer than that by surface pumping (Cui and Jia, 2018). However, current theoretical models of the pumping-induced settlement remain unavailable to fully characterize the abovementioned influencing factors (Budhu and Adiyaman, 2010;Wang et al, 2018;Xu et al, 2012;Zhang et al, 2017;Zhou et al, 2017). Therefore, concerning extracting deep groundwater scenarios, current models still have to be deliberately calibrated by the field measurements (Shen and Xu, 2011;Xu et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%